2013
DOI: 10.1002/phar.1223
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Quality Implications of Opioid‐Based Postsurgical Pain Control Using Administrative Claims Data from a Large Health System: Opioid‐Related Adverse Events and Their Impact on Clinical and Economic Outcomes

Abstract: Opioid use was ubiquitous among hospitalized patients who underwent common surgical procedures. The observed negative outcomes of ORADEs and their impact on patients and the health care system should be considered when evaluating the balance between effectively managing postsurgical pain while minimizing the risk of ORADEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
262
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(280 citation statements)
references
References 38 publications
(82 reference statements)
8
262
0
Order By: Relevance
“…14,15,[17][18][19][20] The frequency of postoperative ORADEs also poses a significant economic burden and strain on resources to hospitals and health care providers. For example, respiratory depression and nausea/vomiting require increased monitoring by the nursing staff and increased utilization of supportive care therapies such as antiemetics.…”
Section: Study Design and Sample Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15,[17][18][19][20] The frequency of postoperative ORADEs also poses a significant economic burden and strain on resources to hospitals and health care providers. For example, respiratory depression and nausea/vomiting require increased monitoring by the nursing staff and increased utilization of supportive care therapies such as antiemetics.…”
Section: Study Design and Sample Selectionmentioning
confidence: 99%
“…11 Previously demonstrated patient-specific ADE risk factors include older age, male gender, race/ethnicity, smoking status, obesity, and comorbid diagnoses such as obstructive sleep apnea (OSA), chronic obstructive pulmonary disease (COPD), renal and hepatic function, cardiac dysrhythmia, degenerative joint disease (DJD), and benign prostatic hyperplasia (BPH). 6,[12][13][14][15] Medication error, which is common with opioid delivery systems, also contributes substantially to the risk of developing an ORADE. 16 • Opioid-related adverse drug events (ORADEs) are common causes of hospitalizations and increased health care costs.…”
mentioning
confidence: 99%
“…Despite its success improving the quality of life of patients with arthritis [31], pain after TKA can sometimes be severe and difficult to control [1]. Clinical studies have shown that severe postoperative pain can be associated with an increased risk of complications, including rehabilitation delay [59], prolonged return to normal functioning [27,28], progression to persistent pain states [46,68], prolonged hospital stay [49], and increased readmission rate [21], all of which can lead to increased cost of care [4,42,62,69].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the mechanisms underlying this variability can help identify susceptible patient populations. Opioid-related adverse events occur in approximately 15% of postoperative patients in the clinical setting (Kessler et al, 2013) and represent a subset of VDRs that may be attenuated by considering altered function of opioid metabolizing enzymes and transporters (Fujita et al, 2010).…”
Section: Introductionmentioning
confidence: 99%